Major increases in teachers’ performance evaluations: Evidence from student evaluation of teaching surveys - Prieto, Jaime; Guede-Cid, Rocío; Cid-Cid, Ana I.; Leguey, Santiago (Tuning Journal for Higher Education, 2023)
Purpose: This exploratory study examined major increases in teachers’ performance evaluations and their immediate impact on next year’s score for those instructors that taught the same subject for at least two years in a row. The purpose was twofold. Firstly, to identify those Student Evaluation of Teaching (SET) survey items associated with major increases in teacher evaluations. Secondly, to examine if there is evidence of the use of these SET results by instructors to improve their teaching.Design: The sample comprised SET survey ratings from one university over a five consecutive year period, for a total sample of 13,052 teacher evaluations and 3,893 teachers-subject observations under analysis. Frequency tables and Student’s t-test were used for analysis.Findings: The results highlighted the three SET survey items captured by the dimension of teaching methodology as those most closely related to major increases in teacher evaluations. Regarding the second objective, the results show no generalised response from teachers who experience major increases in SET ratings. This suggests that the use of SET results is either limited or does not have an immediate measurable effect on student satisfaction.Originality/Value: To the best of our knowledge, this was the first study to specifically examine major increases in teachers’ performance evaluations and their immediate impact on next year’s score based on evidence from SET surveys. Received: 22 December 2021Accepted: 26 February 2023